Anaphylaxis in Pregnancy: A Population-based Multinational European Study. Issue 3 (September 2021) - McCall, S.J; Bonnet, M.P.; Ayras, O.; Vandenberghe, G.; Gissler, M.; Zhang, W.H.; Van Leeuw, V.; Deneux-Tharaux, C.; Kurinczuk, J.J.; Knight, M.
Abstract : ( Anaesthesia . 2020;75:1469–1475) Anaphylaxis is an immunoglobulin E–mediated event that occurs without warning after exposure to an inciting antigen. In pregnancy, this rare condition may result in severe maternal and fetal morbidity and mortality, as it has multisystemic effects. Limited high-quality studies exist regarding anaphylaxis during pregnancy. As the occurrence is rare in a single nation's population, this European multinational study used prospective and retrospective data collection methods to estimate the causative agents, incidence, management, and outcomes of anaphylaxis during pregnancy.